WEB-BASED LIBRARY INFORMATION SYSTEM IN MADRASAH IBTIDAIYAH NEGERI SURAKARTA - Dedi Gunawan; Ivanovick Abdurrakhman Ar Raniri; Robby Nugroho Setyawan; Yogatama Dwi Prasetya (Informatika, Universitas Jenderal Soedirman, 2021)
Library is a primary supporting facility in any level of education spanning from elementary school, middle school and higher education i.e., university. The main aim of library is providing facility in which it can improve educational quality and allow the member to advance their knowledge from various reference sources. Managing book circulation is a crucial aspect for library in which it further increases effectivity for its business process such as returning and borrowing books. However, Madrasah Ibtidaiyah (MI) Negeri Surakarta does not have any such application system which can help its library management, as a result the library member cannot obtain have updated information related to the library collection. Currently, the school relies on manual procedure where the library staff records borrowing and returning books activities in a certain book log. Unfortunately, the manual procedure causes missing data and data consistency in the recording book. Therefore, research aim to design and build e-library. The e-library is a web-based information system that has specific features that can address the school problems. To realize objective, we adopt waterfall software development method to build the information system. We also evaluate our design by using black box testing to ensure its functionality. Results show that our developed system works as it is designed and can handle any request from user without causing any errors.